Inhibitory effects of non-thermal atmospheric plasma on Yersinia enterocolitica and Staphylococcus aureus in the Korean traditional non-fermented kimchi “Geotjeori” - So Hee Kim; Sung-Hee Park; Sung Gi Min; Shin Young Park (Heliyon, 2023)
Food-borne bacteria have frequently been detected in kimchi, a representative and traditional fermented ethnic food of Korea. This study investigated the effect of atmospheric dielectric barrier discharge (DBD) plasma treatment (1.1 kV, 43 kHz, N2: 1.5 m/s, 5–60 min) on reduction of Yersinia enterocolitica and Staphylococcus aureus and on quality parameters in Geotjeroi, a non-fermented kimchi. A decrease of 0.12/0.09, 0.19/0.19, 0.34/0.45, 0.64/0.72, and 1.13/1.12 log10 CFU/g was observed by 5, 10, 20, 30, and 60 min of DBD plasma, respectively. D-value of 52.83 and 51.95 min was determined for Y. enterocolitica (R2 = 0.99) and S. aureus (R2 = 0.98) using the first order kinetics model. The quality parameters (pH, Brix, and hardness) were not significantly different (P > 0.05) between treated and untreated Geotjeori. Moreover, a decrease of >1 log10 CFU/g, for both bacteria was observed without any change in the quality of Geotjeori. These findings imply that DBD plasma treatment enhances Geotjeori safety and protects product from microbial risk.